Depression in the elderly: a literature review study from 2013 to 2020 (Research, Society and Development, 2022)
The present study aimed to analyze depression in the elderly and discuss the triggering and aggravating factors. Depression is one of the main public health problems and is characterized by a disease that has symptoms such as a feeling of frequent sadness and loss of the ability to feel pleasure or joy. Some studies show that functional impairment can be a risk factor for the onset of the disease in the elderly population, however, such depressive symptoms can lead to loss of functionality. Physical exercise programs seem to have a positive response in reducing these symptoms. The reduction in the symptoms of depression through the practice of physical exercise may be related to the increased release of hormones such as endorphins, dopamine, serotonin, providing a tranquilizing effect and a feeling of well-being, obtaining a relaxing post-exercise result. It was a literature review, based on the search for articles published between 2013 and 2020. The databases used will be: SCIELO (Scientific Electronic Library Online); Academic Google.